EFEKTIVITAS KEBIJAKAN SERTIFIKASI GURU (Suatu Studi di SMA Negeri I Manado) - Veronika, Stevi Wanda (JURNAL ADMINISTRASI PUBLIK, 2014)
Teaching license is a certification procces for teachers who have the requirements, like an academic qualifications and professional competence of teachers. So, the teaching license policy should increase the professionalism of the teachers. But the implementation, it doesn't work, the teaching license has so many weakness. Based from it, this research was conducted for answer the question "Is the Teaching licenseÂ  effective to realizing and improving the professionalism of teachers in SMA Negeri 1 Manado?" this research using qualitative methods. The effectivity of Teaching license to realizing and improving the professionalism of teachers shown from enhancement teacher's competence ( individuality competence, teaching management, professionalism, social competence) and professional attitude. This research informant is fifteen teachers from SMA Negeri 1 Manado, one school principal and two students on the XII grades. Primary data take from interview, and the analysis using qualitative technique, interactive model. This study shown: (1) Teaching license can improve the teacher's self-competence be more good, stable, mature, and prestigious; (2) Teaching license can make their teaching management better; (3) Teaching license can improve the professionalism competence like mastering scientific substance, structure and the methods of their own subject; (4) Teaching license can increase the social competency like interaction with the students, their parents and the fellow teacher; (5) And the Teaching license also can developing the professionalism quality like desire to show the ideal attitude, improve and keep the teacher's image, and the pride as a teacher. Based from the research, there is a conclusion that the Teaching License is effective to improving the professionalism quality of teachers. from that conclusion, there is some advice: (1) The Teaching license policy must be develope; (2) Departement of Education and Culture must be objective to giving the Teaching license; (3) The quality of certification process from the college must be enhanced. Keywords: Teaching license policy, teacher's professionalism.